THE IMPORTANCE AND BENEFITS OF WATER PURIFICATION FOR BOILERS (Web of Technology: Multidimensional Research Journal, 2024)
Water treatment in the thermal power industry is an effective way to maintain and increase the efficiency of the heating system, extend the service life of equipment, and save fuel and energy. Water, which is used as the main coolant, must enter the system purified from mechanical impurities, organics and surfactants, dissolved salts, including silicates. Otherwise, the boilers may become unusable, and the heat exchangers will not be able to perform their functions. This article presents the main solutions to the problems of unusability of boiler installations.